2005
DOI: 10.1172/jci200523424
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte-derived collagen VI affects early mammary tumor progression in vivo, demonstrating a critical interaction in the tumor/stroma microenvironment

Abstract: The interactions of transformed cells with the surrounding stromal cells are of importance for tumor progression and metastasis. The relevance of adipocyte-derived factors to breast cancer cell survival and growth is well established. However, it remains unknown which specific adipocyte-derived factors are most critical in this process. Collagen VI is abundantly expressed in adipocytes. Collagen -/-mice in the background of the mouse mammary tumor virus/polyoma virus middle T oncogene (MMTV-PyMT) mammary cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 38 publications
4
67
0
1
Order By: Relevance
“…The fat tissue secretes and/or produces a number of biologically active substances (14), commonly named adipo(cyto)kines (15). Several studies have suggested that adipocyte secreted proteins could stimulate proliferation in malignant cells (16)(17)(18). Further, estrogens synthesized from androgens by the aromatase enzyme in peripheral adipose tissues ; continuous), age at mammography (5-y interval), breast cancer family history (none, first degree, second degree), age at menarche (V13 y, >13 y), number of full-term pregnancies (0, 1-2, z3), age at first full-term pregnancy (<30 y, z30 y), menopausal status and use of hormone replacement therapy (premenopausal, postmenopausal and: current estrogen therapy, current estrogen plus progestin therapy, ex-estrogen therapy, ex-estrogen plus progestin therapy, never hormone therapy), and race.…”
Section: Discussionmentioning
confidence: 99%
“…The fat tissue secretes and/or produces a number of biologically active substances (14), commonly named adipo(cyto)kines (15). Several studies have suggested that adipocyte secreted proteins could stimulate proliferation in malignant cells (16)(17)(18). Further, estrogens synthesized from androgens by the aromatase enzyme in peripheral adipose tissues ; continuous), age at mammography (5-y interval), breast cancer family history (none, first degree, second degree), age at menarche (V13 y, >13 y), number of full-term pregnancies (0, 1-2, z3), age at first full-term pregnancy (<30 y, z30 y), menopausal status and use of hormone replacement therapy (premenopausal, postmenopausal and: current estrogen therapy, current estrogen plus progestin therapy, ex-estrogen therapy, ex-estrogen plus progestin therapy, never hormone therapy), and race.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest are the specific interactions of transformed ductal epithelial cells with the mammary fat pad, relevant for the developmental aspects as well as for the wellestablished dependence of mammary tumors on adipose tissue during early stages of lesion growth. Our recent work on collagen VI has underlined the importance of this extracellular matrix component, which is highly enriched in adipose tissue for the growth of such mammary ductal epithelial tumors (18).…”
Section: Adipose Tissue: From Storage To Endocrine Organmentioning
confidence: 99%
“…These adipocytes can release protein and lipid derivatives that are highly proangiogenic and have an impact on the preexisting vasculature. Finally, the unique extracellular matrix environment of adipose tissue hosts a number of additional cells such as macrophages and offers unique growth potential for transformed cells such as breast cancer cells (18,19).…”
mentioning
confidence: 99%
“…Laminin-111/Ln-1 has three head domains which can crosslink into a soft cohesive 3D network, whereas other laminin isoforms with truncated head domains, such as laminin-332/Ln-5, laminin-511/Ln-10 or laminin-521/Ln-11, cannot form a network [22,29], and do not support normal epithelial cell function in vitro, despite the fact that all these isoforms present similar tail domains to cells [16]. Furthermore, some evidence suggests that laminin-332, or collagen IV may support tumor invasion or aggressiveness [30][31][32].…”
Section: The Basement Membrane In the Normal Breast Is A Tumor Supprementioning
confidence: 99%